Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ra01132e
|View full text |Cite
|
Sign up to set email alerts
|

MnO2/carbon nanowall electrode for future energy storage application: effect of carbon nanowall growth period and MnO2mass loading

Abstract: MnO2/carbon nanowalls electrode with a specific capacitance of 1170 F g−1, energy density of 162.5 W h kg−1 and power density of 915.7 W kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…CNW, also known as vertically oriented/aligned graphene sheets, are on long‐term stable, as far as structure and morphology are concerned, even when used in working devices. This nanomaterial has good durability over long‐time testing in acid solution, and functional stability when used in field emitters, electrodes for biosensors, and gas sensors, or as nanostructured electrodes in batteries, and supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…CNW, also known as vertically oriented/aligned graphene sheets, are on long‐term stable, as far as structure and morphology are concerned, even when used in working devices. This nanomaterial has good durability over long‐time testing in acid solution, and functional stability when used in field emitters, electrodes for biosensors, and gas sensors, or as nanostructured electrodes in batteries, and supercapacitors …”
Section: Introductionmentioning
confidence: 99%
“…MnO 2 NPs were anchored on VAGNAs (synthesized on Ni foams) via electrodeposition, and the hybrid pseudocapacitor electrodes delivered much improved capacitance as compared with both pure MnO 2 and VAGNA electrodes. [95,96] The density functional theory calculations indicated that the morphology of VAGNAs and the covalent bonding between MnO 2 and graphene contributed to effective charge transfer during the electrochemical processes. [94] As a representative pseudocapacitive material, porous RuO 2 NPs were also decorated on VAGNAs/ Si through electrodeposition, and the electrodes were used for fabricating all-solid-state micro-supercapacitors (as shown in the SEM image in Figure 7a).…”
Section: Faradaic Pseudocapacitorsmentioning
confidence: 99%
“…Porous carbon materials, transition metal oxides, and conducting polymers are currently the promising candidates for supercapacitor electrode materials [5]. Among various metal oxides, manganese oxides are one of the most promising pseudocapacitive materials due to their high specific capacitance, environmental compatibility and cost effectiveness [6,7]. In particular, -type manganese oxide has gained much attention as a potential electrode material for supercapacitors due to its layered structure and unique properties [8,9].…”
Section: Introductionmentioning
confidence: 99%